Developing information technology & operational technology configuration management in pharmaceutical industry - Tuohimaa, Kristian (My University, 2020)
Complex information systems and different types of hardware create the need for proper configuration management in various manufacturing companies. Along with the other IT service management processes, configuration management provides a basis for efficient manufacturing IT operations. The processes guide decision making with accurate information and help to reduce costs. In the strictly regulated pharmaceutical industry, predetermined processes must be followed to guarantee the compliance of operations regarding information technology and operational technology. In addition to configuration management, the processes in scope include asset, change, and incident management. The interoperability between the relevant activities can be enhanced if the processes are executed in a single system. The objective of this master's thesis is to improve configuration management and the activities associated with it in the target company. The need for a new configuration management database was identified at an early stage and the desired features, roles, and rules were collected from the IT personnel. Relevant academic literature and applicable regulatory requirements were studied to achieve system compliance. The information from various sources was then transformed into a user requirements specification and the requirements quality was formally assessed. The assessment showed that the quality, accuracy, and compliance of the user requirements specification was increased thus indicating an enhancement in the target company's future configuration management and the activities associated with it. The performance assessment metrics for the specified software product were also gathered and classified to assist in the assessment of the configuration management software after its implementation.